CORRELATION BETWEEN HOUSE DUST MITE DENSITY WITH HEALTHY HOUSE CRITERIA AND ASTHMA STATUS IN PEDIATRIC PATIENTS - Shobrina Insan Sakina Armunanto; Dian Puspita Dewi; Dodik Pramono; Moh Syarofil Anam (Jurnal Kedokteran Diponegoro)
Abstract